2013
DOI: 10.1016/j.appdev.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Work characteristics and fathers' vocabulary to infants in African American families

Abstract: Fathers’ vocabulary to infants has been linked in the literature to early child language development, however, little is known about the variability in fathers’ language behavior. This study considered associations between fathers’ work characteristics and fathers’ vocabulary among a sample of employed African American fathers of 6-month old infants who were living in low-income rural communities. After controlling for family and individual factors, we found that fathers who worked nonstandard shifts and repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 77 publications
1
9
0
1
Order By: Relevance
“…On the other hand, when considering all factors together, only the fathers' educational level and working status appear to be associated with the children's I-BST performance. These data are noteworthy and further support previous reports on the effect of fathers' vocabulary and employment on language development of their children [22,23,24,27]. In addition, the findings suggest that fathers' educational level and working status might play a role in the development of children's narrative abilities.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…On the other hand, when considering all factors together, only the fathers' educational level and working status appear to be associated with the children's I-BST performance. These data are noteworthy and further support previous reports on the effect of fathers' vocabulary and employment on language development of their children [22,23,24,27]. In addition, the findings suggest that fathers' educational level and working status might play a role in the development of children's narrative abilities.…”
Section: Discussionsupporting
confidence: 80%
“…In particular, parents' work environments impact child development through their influence on family processes including the interactional contexts in which children learn much of their earliest language [26]. A recent study by Pancsofar et al [27] found that fathers' employment influences the vocabulary input of their children. It seems, therefore, important to take into consideration both years of education and parents' employment when analyzing factors associated with narrative abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, there has been an increase in research on father involvement in children’s education and learning (Cabrera & Tamis-LeMonda, 2014; Lamb, 2010). Recent research has moved away from unidimensional characterizations of fathers that focused on father presence or absence to a broader consideration of the many roles fathers play in the developmental and educational experiences of their children (Lamb, 2010; Pancsofar, Vernon-Feagans, Odom, & The Family Life Project Investigators, 2013). However, this extant literature remains almost exclusively focused on fathers of typically developing children, while very few studies have considered the school involvement experiences of fathers of children with disabilities, and even fewer studies considering fathers of children with complex disabilities.…”
mentioning
confidence: 99%
“…However, recent studies on paternal language have shown that fathers also contribute to their children's language development (e.g. Tamis-LeMonda, Shannon, Cabrera, & Lamb, 2004;Duursma, Pan, & Raikes, 2008;Pancsofar & Vernon-Feagans, 2006, 2010Pancsofar et al, 2013;Duursma, 2014).…”
Section: Introductionmentioning
confidence: 99%